Parents' perspective on COVID-19 vaccine in children 6 months through 4 years: a cross-sectional study from Northwest Wisconsin. Issue 9 (17th September 2022) - Mangat, Chetna; Rich, Jennifer; Sanghavi, Devang; Schmidt, Rebecca; Milosavljevic, Natasa; Linh, Tran; Bansal, Pankaj
Abstract : Vaccination is critical to control the ongoing COVID-19 pandemic, but despite the availability of safe and effective vaccine in children over 5 years, vaccination rates remain low. There is paucity of data about vaccine acceptance and factors influencing parents' hesitancy about the COVID-19 vaccine for young children. Aims and objectives: To estimate vaccine acceptance by parents of children 6 months through 4 years, and to evaluate the factors influencing vaccine hesitancy. Methods: Electronic survey was sent to parents of children 6 months through 4 years through an online portal account at Mayo Clinic Health System, Northwest-Wisconsin. Data were captured via Research Electronic Data Capture secured data collection software. Bivariate and multivariate regression was used to determine most pertinent factors influencing parents' decisions against the outcome, 'Intent to Vaccinate'. Results: 39.7% of the parents were 'very likely' or 'somewhat likely ' to vaccinate their children once the vaccine became available, while 49.8% were not likely or highly unlikely to vaccinate. Routine childhood vaccination, receiving seasonal influenza vaccine, parents' perception of COVID-19 severity in children and safety and effectiveness of the vaccine were all associated with more vaccine acceptance. 71.4% of parents who will likely not vaccinate their children indicated that they are unlikely to change their decision. The need for more research on the vaccine and more information from the PCP office were the most common reasons behind the vaccine decision-making. Conclusions: Vaccine hesitancy remains a major issue regarding uptake of the upcoming COVID-19 vaccine. Strong and clear evidence-based recommendations from primary care provider and more information from trusted websites such as Centers for Disease Control and Prevention can decrease vaccine hesitancy in parents. Further research targeted at understanding beliefs and perspectives of parents from different demographics can assist policy-makers in implementing measures to improve vaccination rates in children and tailor our dialogue to match the needs of our patients and families.